Analysis of New Autonomous Regional Policies in Indonesia - Adithya Raidipa Wisesa; Rahmat Salam; Izzatusholekha (Global Writing Academica Researching and Publishing, 2023)
The size of the Indonesian state makes it difficult to create a centralized government system. Moreover, Indonesia is an archipelagic state, where the islands are separated by sea. Therefore, it is necessary to implement a new autonomous region policy to maintain the welfare of the Indonesian state. This study then aims to analyze the New Autonomous Region Arrangement Policy process in Indonesia. This research will be carried out using descriptive qualitative methods. The selection of this method is expected to describe and summarize various conditions, situations, or phenomena of social reality that exist in society. The data source used in this study comes from documentation and observation. The results of this study then found that interests had an important role in forming the New Autonomous Region (DOB). In structuring the new autonomous regions, there are positive and negative sides. Unfortunately, in establishing a new autonomous region, the expected degree of change has not been fully realized. Several factors hamper this process, such as the low quality of human resources and inadequate financing.